John Lackey Brown, public diplomat par excellence - Raphaël Ricaud (Caliban: French Journal of English Studies)
American public diplomacy is a hard-to-define but often-used phrase which refers to the ways in which Washington seeks to influence domestic and foreign audiences through semi or unofficial channels. Throughout the 20th century, it has taken on various forms. Some argue public diplomacy is a euphemism for white propaganda. Others claim it is an alternative form of diplomacy. This study tackles the issue by delving into the life of a much-hailed but wildly understudied public diplomat: Dr. John Lackey Brown.During the later years of the First World War, the Creel Committee generated propaganda which, given today’s standards, appears too simplistic to be efficient. During the Cold War, however, the United States Information Agency devised more subtle ways to "tell America’s story to the world." The use of culture as a weapon to win over hearts and minds is well-documented. Less documented, however, is the study of public diplomats who did not see themselves as propagandists. This article is therefore an inquiry of what made John Lackey Brown a public diplomat. I argue that it was not the tasks that he performed on the job per se that generated good public diplomacy.